Risk of Fracture With Dipeptidyl Peptidase-4 Inhibitors, Glucagon-like Peptide-1 Receptor Agonists, or Sodium-Glucose Cotransporter-2 Inhibitors in Patients With Type 2 Diabetes Mellitus: A Systematic Review and Network Meta-analysis Combining 177 Randomized Controlled Trials With a Median Follow-Up of 26 weeks - Chai, Sanbao; Liu, Fengqi; Yang, Zhirong; Yu, Shuqing; Liu, Zuoxiang; Yang, Qingqing; Sun, Feng (Frontiers in Pharmacology, 2022)
Aim: To investigate the association between the use of dipeptidyl peptidase-4 inhibitors (DPP-4i), glucagonlike peptide-1 receptor agonists (GLP-1 RAs), or sodium-glucose cotransporter-2 inhibitors (SGLT-2i) and the risk of fracture among patients with type 2 diabetes mellitus. Methods: Medline, Embase, Cochrane Library and Clinical-Trials.gov databases were searched for randomized controlled trials (RCTs). Network meta-analysis was performed for total fracture and a series of secondary outcomes. Results: A total of 177 RCTs (n = 165 081) involving risk of fracture were identified (a median follow-up of 26 weeks). DPP-4i, GLP-1 RAs, and SGLT-2i did not increase total fracture risk compared with insulin (odds ratio : 0.86, 95% confidence interval 0.39 to 1.90; 1.05, 0.54 to 2.04; 0.88, 0.39 to 1.97, respectively), metformin (1.41, 0.48 to 4.19; 1.72, 0.55 to 5.38; 1.44, 0.48 to 4.30), sulfonylureas (0.77, 0.50 to 1.20; 0.94, 0.55 to 1.62; 0.79, 0.48 to 1.31), thiazolidinediones (0.82, 0.27 to 2.44; 1.00, 0.32 to 3.10; 0.83, 0.27 to 2.57), α-glucosidase inhibitor (4.92, 0.23 to 103.83; 5.99, 0.28 to 130.37; 5.01, 0.23 to 107.48) and placebo (1.04, 0.84 to 1.29; 1.27, 0.88 to 1.83; 1.06, 0.81 to 1.39). Conclusions: The use of DPP-4i, GLP-1 RAs, or SGLT-2i is unlikely to increase the risk of fracture among type 2 diabetes mellitus.